Using Digital Storytelling As A Tool To Enhance English Writing Skills Among School Students Can Be Highly Effective - Wahyu Oktarius Putra; Dina Ulanda; Lira Meista (PT. Intelek Cendikiawan Nusantara, 2024)
This study explores the potential of digital storytelling as a novel approach to bolstering English writing abilities among schoolchildren. Writing is a cornerstone of effective communication, yet many students struggle with it due to limited exposure and grammatical challenges. Conventional teaching methods often fall short in captivating students and overcoming these obstacles. Digital storytelling, a fusion of multimedia and narrative, offers a dynamic learning environment that can enhance writing proficiency. By employing pre- and post-tests on a group of 25 students, this research evaluated the impact of digital storytelling. The results unequivocally demonstrate significant improvements in writing skills, characterized by higher test scores and enhanced ability to structure and articulate ideas. These findings corroborate previous research emphasizing the effectiveness of digital storytelling in fostering language skills and critical thinking. This study posits that digital storytelling is a potent tool for teaching writing, providing an immersive and rewarding learning experience. It is recommended that educators integrate this method into writing curricula to optimize student outcomes. Future research should investigate the long-term effects of digital storytelling and its adaptability to diverse educational settings.